Nilai Ekonomi Objek Wisata Alam Pantai Lubang Buaya Di Negeri Morella Kabupaten Maluku Tengah - Pratiwi, Herlina W.; Iskar, Iskar; Silaya, Thomas M. (MAKILA, 2019)
A natural tourism object is a form of tourism activity that utilizes the potential of natural resources and environmental management. The economic valuation of natural tourism needs to be done to see the value of the existence of nature tourism, which is sometimes valued. One method that can measure the economic value of a tourist area is the Travel Cost Method (TCM). Therefore this study aims to analyze the economic value of the natural tourism object of Lubang Buaya Beach in Negeri Morella, Central Maluku Regency. The results showed that the travel cost (Travel Cost) obtained 69,220 travel costs/person/visit, and the economic value of OWA Lubang Buaya Beach is Rp. 83,064,000 / year. OWA Lubang Buaya Beach in the perception of visitors is a safe place of recreation, beautiful natural beauty, and easy accessibility. It's just that the layout is not good, and tourism facilities are incomplete. So the need for additional facilities and better management. The results of the study of the attraction of beach attractions obtained only elements of beauty and comfort have all aspects of the assessment of the seven elements of the assessment criteria.